Analisis Usaha Budidaya Pembesaran Ikan Nila (Oreochromis niloticus) di Desa Jembayan Kecamatan Loa Kulu Kabupaten Kutai Kartanegara - Yudha Ambara; Helminuddin; Bambang Indratno Gunawan (2339-1324, 2023)
This study aimed to analyze the business feasibility of Nile tilapia (Oreochromis niloticus) grow-out farms in Jembayan Village, Loa Kulu, Kutai Kartanegara. Sampling was done using the Purposive Sampling technique with a total respondent of 15 people. The data analysis method used quantitative analysis, while the business feasibility analysis used Revenue, Income, Break-Even Point (BEP), Revenue Cost Ratio (RCR), Payback Period (PP), and Return On Investment (ROI). The result showed that the Nile tilapia grow-out farm business gained revenue of IDR 14,272,000/Production or IDR 42,816,000/year and received an income of IDR 7,867,576/Production or IDR 23,602,729/year. The result of calculating the Nile tilapia grow-out farm business was feasible to be maintained with a BEP in sales of IDR 12,256,078 and a BEP in units of 738 kg, while a BEP selling price of IDR 17,822/kg. The result of calculating the Nile tilapia grow-out farm business showed that it was feasible to be maintained and developed with an average value of RCR of 1.80. The result of calculating PP for identifying the amount of time required to recoup the funds expended for investment was 1.4 years and an ROI of 70.6%. Therefore, the Nile tilapia grow-out farm is feasible to be operated since the ROI percentage is higher than the interest percentage of Bank BRI of 6%/year (deposit interest rate of Bank BRI in 2021).